2021
DOI: 10.3390/ijerph18041465
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Maternal Experiences of Interpersonal Discrimination and Adverse Birth Outcomes: A Systematic Review of the Evidence

Abstract: In the present systematic review, we argue that maternal experiences of interpersonal discrimination at least partially account for the disproportionate rates of adverse birth outcomes in minority populations. Since the 1990s, research in this area has slowly, but steadily increased, shedding more light on the insidious nature of interpersonal discrimination and its toxic health effects. With the aim of bringing this topic to the fore in academic as well as clinical settings, this paper provides a state-of-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 72 publications
0
36
0
Order By: Relevance
“…Lifetime experiences of discrimination, including witnessing a caregiver discriminated against, have been linked to having an infant with LBW (Larrabee Sonderlund et al, 2021). Although LBWs were more closely tied to growing up in the United States as a young child than with prenatal discrimination, the discrimination node indirectly enabled the connection between greater acculturation and LBW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifetime experiences of discrimination, including witnessing a caregiver discriminated against, have been linked to having an infant with LBW (Larrabee Sonderlund et al, 2021). Although LBWs were more closely tied to growing up in the United States as a young child than with prenatal discrimination, the discrimination node indirectly enabled the connection between greater acculturation and LBW.…”
Section: Discussionmentioning
confidence: 99%
“…This cycle may begin in early childhood, whereby early psychosocial stress may become biologically embedded through epigenetic mechanisms (Miller et al, 2011). The resulting pro‐inflammatory state may underlie multiple stress‐related health conditions, including depressive symptomology and obstetric complications during the child‐bearing years (Larrabee Sonderlund et al, 2021). In this way, childhood exposures as women arrive and acculturate to the United States may increase not only biological vulnerability to depressive symptoms but vulnerability to having an infant with LBW.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence links multiple types of racism-related adversity to adverse birth outcomes. Regarding interpersonal discrimination, a recent systematic review from 2021 examined 28 studies on the relation between maternal experiences of interpersonal discrimination and pregnancy or birth related outcomes ( 23 ). Authors concluded that the majority of these studies provide evidence that maternal experiences of interpersonal discrimination predict adverse birth outcomes ( 23 ).…”
Section: The Contribution Of Racism-related Stress and Adversity To D...mentioning
confidence: 99%
“…Racism is a stressor that affects health due to the cumulative effects of discriminatory experiences throughout the life course, at multiple levels, and is associated with adverse reproductive outcomes such as pre-term birth and low-birth weight ( Sonderlund et al, 2021 ). Racism refers to prejudiced positions and practices at multiple levels, that perpetuate oppression and inequality by restricting opportunities for non-White groups to the advantage of White groups ( Braveman et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%